Preparation And Characterization Of Absorbent Prepared From Coal Fly Ash For Sulfur Dioxide (SO2) Removal. - Lee, Keat Teong; Bhatia, Subhash; Mohamed, Abdul Rahman (2003)
Active absorbent for flue gas desulfurization was prepared from coal fly ash, calcium oxide and calcium sulfate by steam hydration. The absorbent was examined for its macro and micro-structural properties.